2021
DOI: 10.12973/ijem.7.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Impromptu Speaking Skills of Pre-service Teachers

Abstract: <p style="text-align:justify">The purpose of the study is to examine pre-service teachers' impromptu speaking skills on the basis of the evaluations of the instructor, peers and their own. The study employed a descriptive case study design, one of the qualitative research methods. A total of 23 pre-service math teachers taking the course of Art of Effective Speech in a state university in Turkey in the 2016-2017 academic year participated in the study. The data of the study were collected through the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Communication skills can also effectively increase teacher-student interaction (Hattie, 2015). However, it is still found that teachers and prospective teachers feel less able to use speaking skills because they do not have adequate experience (Aktay, 2021). Student organizations can be a supportive environment for training public speaking and teaching skills for prospective teachers (Hébert & Hauf, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Communication skills can also effectively increase teacher-student interaction (Hattie, 2015). However, it is still found that teachers and prospective teachers feel less able to use speaking skills because they do not have adequate experience (Aktay, 2021). Student organizations can be a supportive environment for training public speaking and teaching skills for prospective teachers (Hébert & Hauf, 2015).…”
Section: Introductionmentioning
confidence: 99%